2006
DOI: 10.1111/j.1745-9125.2006.00067.x
|View full text |Cite
|
Sign up to set email alerts
|

Sex-Based Disparities in Felony Dispositions Before Versus After Sentencing Reform in Ohio

Abstract: Extending Koons‐Witt's (2002) study of whether sex‐based disparities in imprisonment likelihoods changed under sentencing guidelines in Minnesota, we examined similar models for Ohio with additional analyses of felony conviction likelihoods and sentence length for 5,472 felony defendants from twenty‐four trial courts. The main effects of a defendant's sex on imprisonment were significant during both periods (unlike the Minnesota findings), consistent with a chivalry perspective. Random coefficient models revea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
124
3

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(133 citation statements)
references
References 46 publications
6
124
3
Order By: Relevance
“…Other results consistent with extant findings for imprisonment include the much stronger effects of legal factors relative to extra-legal factors (e.g., Miethe, 1987;Steffensmeier et al, 1998;Ulmer, 1997;Wooldredge, 2009), and the significance of extra-legal effects including sex, age, education, means of support, residence length, and the interaction between a defendant's race, sex, and age (recent support for three or more of these factors include Doerner & Demuth, 2010;Griffin & Wooldredge, 2006;Holleran & Spohn, 2004;Johnson, 2005Johnson, , 2006Koons-Witt, 2002;Muhlhausen, 2004;Spohn & Holleran, 2000;Steffensmeier & Demuth, 2000Tapia, 2010;Ulmer et al, 2010;Ulmer & Johnson, 2004;Wooldredge, 2007).…”
Section: Discussionmentioning
confidence: 59%
“…Other results consistent with extant findings for imprisonment include the much stronger effects of legal factors relative to extra-legal factors (e.g., Miethe, 1987;Steffensmeier et al, 1998;Ulmer, 1997;Wooldredge, 2009), and the significance of extra-legal effects including sex, age, education, means of support, residence length, and the interaction between a defendant's race, sex, and age (recent support for three or more of these factors include Doerner & Demuth, 2010;Griffin & Wooldredge, 2006;Holleran & Spohn, 2004;Johnson, 2005Johnson, , 2006Koons-Witt, 2002;Muhlhausen, 2004;Spohn & Holleran, 2000;Steffensmeier & Demuth, 2000Tapia, 2010;Ulmer et al, 2010;Ulmer & Johnson, 2004;Wooldredge, 2007).…”
Section: Discussionmentioning
confidence: 59%
“…There is little evidence from those studies to indicate that white women receive preferential treatment relative to other women. In fact, in two separate studies of sentencing outcomes that occurred before and after guidelines implementation, researchers found either no differences between black and white females or differences that favored black females (Griffin and Wooldredge 2006;Koons-Witt 2002). Others have also observed that black and white women are equally likely to be incarcerated (Spohn and Beichner 2000;Spohn and Spears 1997).…”
Section: Prior Empirical Researchmentioning
confidence: 91%
“…In short, racist conceptions of ''femininity'' more closely fit white women (Klein 1995). Consequently, some have speculated that women of color are less likely than white women to be accorded preferential treatment (Brennan 2002(Brennan , 2006Belknap 1996;Farnworth and Teske 1995;Griffin and Wooldredge 2006;Visher 1983;Young 1986). Indeed, studies of media portrayals of female offenders reveal that white women are more likely than minority women to have their criminal behavior excused in some way (Brennan and Vandenberg 2009;Bond-Maupin 1998;Farr 1997Farr , 2000Huckerby 2003).…”
Section: Theoretical Frameworkmentioning
confidence: 94%
“…Furthermore, women defendants tend to arouse less fear, are often seen as less crime-prone, more amenable to treatment and less morally blameworthy, and tend to be the objects of more sympathy (see reviews by Griffin & Wooldredge, 2006;Koons-Witt, 2002;Steffensmeier et al, 1993). Therefore, trials involving women defendants might arouse more sympathy and less negative feelings toward the defendant, and if so, their trial penalties would be correspondingly less.…”
Section: Offense and Offender Characteristicsmentioning
confidence: 93%